NILAI BUDAYA DALAM PEPATAH PETITIH DAYAK NGAJU KALIMANTAN TENGAH - Titik Wijanarti (Multilingual, 2014)
Literatures always contain values that are beneficial to human life both in life as individuals and as social beings. This study examined the content of cultural values in the proverb owned by local people Dayak Ngaju Central of Kalimantan. Method applied are qualitative descriptive and library. Based on research conducted, it is discovered some cultural values embodied in the proverb of Dayak Ngaju. he cultural values are an optimism in living, passion for hard work,adulteryprohibition, advice to do good in life, and keeping the nature in harmony.